আবদুশ শাকুরের বয়ান - শাকুর, আবদুশ; Nomāna, Svakr̥ta (ঢাকা : রোদেলা প্রকাশনী, 2012)
Transcripts of interviews by Ābaduśaa Śākura, 20th century Bengali author from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Śākura, Ābaduśa -- Interviews; Authors, Bengali -- 20th century -- Interviews; Authors, Bengali -- Bangladesh -- Interviews